Impact assessment of COVID-19 non-pharmaceutical interventions in long term care facilities in Cyprus: Safety improvement strategy. (November 2021) - Vogazianos, Paris; Argyropoulos, Christos D.; Haralambous, Christos; Mikellidou, Cleo Varianou; Boustras, George; Andreou, Michalis; Silvestros, Valentinos; Theofanous, Fani; Soteriou, Soteroulla; Gregoriou, Ioanna; Apostolidou, Andri Jaber; Demetriou, Anna; et al.
Abstract: The current COVID-19 crisis has changed our everyday lives almost in every aspect. Many people worldwide have died or hospitalised due to the severe impact of COVID-19 on the vulnerable population, and in particular to the elderly residents of long term care facilities (LTCF). The problem is amplified due to the fact that many of those occupants also suffer from comorbidities (e.g. respiratory and cardiovascular diseases, hypertension, etc.) and are therefore regarded as a susceptible host to severe COVID-19 disease. Impacts can be felt in the wider societal safety level. The aim of the present study is, therefore, to present the first National multimodal quality and safety improvement strategy plan for the LTCF in the Republic of Cyprus. The current program focused on the intensification of COVID-19 epidemiological surveillance, the promotion of educational training on best practises in infection control and prevention, and the implementation of additional non-pharmaceutical interventions (NPIs), according to the recommendations of ECDC (European Centre for Disease Prevention and Control) and WHO (World Health Organization). This innovative program fostered the interconnectivity and collaboration among the local authorities, academia and the local leaders of the LTCF. In addition, this program reinforced the importance of volunteerism and active participation of medical students in the National initiatives against the COVID-19 pandemic. The effectiveness of the adopted multimodal advanced care-safety planning program is appraised based on the reported new confirmed COVID-19 cases among LTCF healthcare workers and occupants, after the introducing and implementation of the selected NPIs. This multimodal strategy plan seems to be capable of reducing significantly the number of new cases of COVID-19 infections in LTCF and as a result, to also affect the residents' death number.